Socio Cultural and Regimen Related Factors Influencing Adherence to Antiretroviral Therapy Among Youth (15-24 Years) in Selected Health Facilities in Nyeri County - Irakoze, Huguette; Nyavanga, Eunice; Juma, Rose (International Journal For Research In Health Sciences And Nursing, 2020)
The number of youths living with HIV is rising globally. In Nyeri County, the prevalence of HIV is reported to be 5.1% and viral load suppression is 77.1%. Adherence continues to pose a serious challenge among the youth receiving antiretroviral therapy; barriers include dosing schedules, pill burden stigma, denial, lack of social support and drug adverse side effect. The study aimed at assessing the socio cultural and regimen related factors influencing adherence to antiretroviral therapy among youth (15-24 Years) in selected health facilities in Nyeri County. A descriptive cross sectional research design was adopted, 227 young people (15-24 years) living with HIV on antiretroviral therapy for more than 6 months were selected from Karatina district hospital, Nyeri referral hospital, and Tumutumu PCEA. Study sites were purposive sampled and the participants were sampled using probability proportionate to size. Quantitative data was collected using structured questionnaires while qualitative data was collected from two focused group discussion (FGD). Qualitative data was analysed using both descriptive and inferential statistical techniques, qualitative data was analyzed using thematic analysis approach. From the results, 115 were females while males were 112. Majority (159) were between the ages of 18-24 years, 215 were single with 155 having attained secondary school education. Most (221) had started medication before 15 years of age. Many (153) were virally suppressed, 135 were supported by the family and community, 96 had not experienced stigma and 151 had not denied their HIV infection status. Community, friends and family support, stigma, denial were significantly associated adherence to ART (<0.05). Regimen related results depicted that (61.8%) took 2 pills per day, 22.4 % more than 2 pills while 15.8 % took only one pill. Further, 29.1 % felt the drug burden while 18.5% reported side effects from the treatment. The number of pills per day was shown to be significantly associated with adherence (p=0.04). The study recommends concerted effort between the patients, family, community, health care providers and policymakers in Nyeri County to reduce stigma and denial. School management should create an enabling environment to help students take drugs regularly and privately. The Ministry of Education to develop strategies and guidelines as part of school-based support systems for HIV infected youth. Acceptance of status and disclosure necessitates good preparation through counselling and support to navigate ongoing challenges due to the lifelong treatment of the HIV. The county needs to strengthen Operation Triple Zero strategy in order to realize 90-90-90 UNAID targets.